Pelatihan Sistem Pembagian Tugas Pencatatan Keluar dan Masuk Barang di Sakura GirlShop - Utami, Ni Made Satya; Sapta, I Ketut Setia; Verawati, Yenny; Sukmayanti, Nyoman Ayu Purnami (Cahaya Pengabdian, 2024)
One of the regional economic forces that support the Indonesian economy is the presence of business actors, Micro, Small and medium enterprises (MSMEs). One of them is the Sakura Girl shop, although many consumers visit, they face the problem of human resources who have not fully understand the distribution of tasks and recording in and out of goods that have not been realized properly due to lack of assistance in the process of checking the stock of goods. Answering these challenges using the Participation Research Action (PRA) method is to discuss with the Owner and employees, by providing assistance and training to existing human resources aimed at improving employees' knowledge, skills, and performance so that there is no social gap between employees.